Preemption of compliance costs and the voluntary adoption of SFAS No. 123(R). Issue 1 (1st July 2014) - Ebrahim, Ahmed; Bradford, Bruce
Abstract : Purpose: – This paper aims to study a preemption proposition for the compliance costs associated with stock option expensing under SFAS 123(R) by examining whether early adopters used their discretion over option pricing model inputs to mitigate the adoption effect. Design/methodology/approach: – The paper uses a matched sample approach of firms that voluntarily adopted stock option expensing during the 2002-2004 period and similar firms that waited until the mandatory expensing. The paper empirically examines some determinants of voluntary adoption, and the changes in option pricing model inputs during the period leading to mandatory expensing. Findings: – The paper reports evidence that voluntary adopters of stock option expensing during the 2002-2004 period have used the period leading to mandatory expensing to preempt its compliance cost effect. The authors exercised their discretion by decreasing estimates for stock price volatility and time-to-maturity to preempt or minimize the reduction in earnings before mandatory adoption date. Originality/value: – Results of this paper are useful to accounting regulators in understanding the reaction of financial statement preparers to deliberations, effective dates and voluntary early adoption terms of the accounting standards setting process.